Clinical characteristics and evolution of syphilis in 24 HIV+ individuals in Rio de Janeiro, Brazil - Gutierrez-Galhardo, Maria Clara; Valle, Gláucia Francesconi do; Sá, Fernanda Cabral de Silva; Schubach, Armando de Oliveira; Valle, Antonio Carlos Francesconi do (Revista do Instituto de Medicina Tropical de São Paulo, 2005)
A total of 24 patients with syphilis and HIV infection were treated from January 1997 to March 2003 at the Infectious Dermatology Outpatient Clinic of the Evandro Chagas Clinical Research Institute, Oswaldo Cruz Foundation, Rio de Janeiro, Brazil. The caseload consisted of 20 males (83.3%) and four females (16.7%), with a mean age of 38.04 years and mean T CD4+ count of 389.5 cells/mL. Syphilis was diagnosed as secondary in 16 (62.5%) patients, late latent in eight (33.3%), and tertiary in one (4.2%). Manifestations of secondary syphilis were palmar and plantar erythematopapulous cutaneous lesions in nine (37.5%), papulous exanthema in four (16.7%), patchy alopecia in 3 (12.5%) and osteochondritis in one patient (4.2%). Tertiary syphilis was characterized by verrucous lesions. Neurosyphilis was diagnosed in four patients (16.7%), with headache as the only manifestation in two patients. Drugs used in treatment included benzathine penicillin, ceftriaxone, erythromycin, and crystalline penicillin. Cure was achieved in 18 patients (75%). Five patients (20.8%) were retreated, three of whom presented a history of re-exposure. This study confirms the importance of establishing the diagnosis of neurosyphilis in patients with HIV infection, in addition to performing follow-up on treatment for syphilis.